Listening Self-Efficacy of EFL Students of Pre-Service Teaching Program in EFL Classroom Setting - Darmawan Labira; Rani; Maria Elisabeth Nona Marsi (Hasanuddin University, 2023)
Listening has been widely recognized, viewed and explored as a theoretical foundation in the realm of language research. Considerable amount of papers found listening self-efficacy in EFL classroom is still a challenging issue. This paper attempted to explore listening self-efficacy of 42 EFL students who enrolled in listening class. The data were collected through 18 self-rated items questionnaire using 5-point Likert-type scale and than measured and analyzed individually before presented them differently in percentage The finding revealed that student’s self-efficacy toward listening skill in direct listening was 39 out of 42 students (92%) were categorized as high self-efficacy while 3 out of 42 students (7%) students were categorized as moderate self-efficacy and students’ self-efficacy in their abilities in complex listening was 75% while self-efficacy on their abilities in dialects listening was 70%. Students with higher self-efficacy posessed higher capabilities in orginizing their materials in a way better performance, more well-prepared before the class started and likely more actively engaged in various classroom activities. In the other hand, one’s with moderate or lower self-efficacy was reflected through less less contribution, encountering difficulties using emotional reactions, approaching difficult tasks as threats to be avoided and being discouraged. Verbal persuasions, observing role model performances, and positive experiences of task accomplishments were a few of most common of student’s source of self-efficcy. Students level of self-efficacy in each students were not affected by gender.